DATA PELAYANAN OBSTETRI NEONATAL EMERGENSI KOMPREHENSIF (PONEK) DI RSUP PROF. DR. R. D. KANDOU PERIODE JANUARI 2014 – JUNI 2015 - Kaligis, Virginia R.; Sondakh, Joice M. M. (e-CliniC, 2016)
Abstract: PONEK is the form of the efforts to provide services for mothers and newborns in an integrated manner. The goal of PONEK is to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Obstacles that slow the decline of MMR and IMR in Indonesia are barriers to the provision and access to emergency obstetric and neonatal care. This was a descriptive retrospective study. The most frequent type of labor is the spontaneous labor with back of the head position. Implementation of IMD (early initiation of breast-feeding) has not reached 100% because it is still focused on normal labor. PMK (kangaroo mother care) services has reached 100%, all BBLR (low birth weight) patients are treated with PMK. The most obstetric disease is premature labor. The most neonatal disease is caput succedaneum. MMR in 2014 was 298 deaths per 100.000 live births, until June 2015 increased 387 deaths per 100.000 live births. IMR for 2014 was 371 deaths per 1.000 live births, until June 2015 increased 453 deaths per 1.000 live births.Keyword: PONEKAbstrak: PONEK merupakan bentuk upaya penyediaan pelayanan bagi ibu dan bayi baru lahir secara terpadu. Tujuan PONEK adalah menurunkan Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB). Kendala lambatnya penurunan AKI dan AKB di Indonesia adalah hambatan terhadap penyediaan dan akses pelayanan kegawatdaruratan obstetri dan neonatal. Penelitian ini menggunakan metode deskriptif retrospektif. Jenis persalinan tersering adalah spontan letak belakang kepala. Pelaksanaan IMD belum mencapai 100% karena masih terfokus pada persalinan normal. Pelayanan PMK sudah mencapai 100% yaitu seluruh pasien BBLR yang dirawat dilakukan PMK. Penyakit kebidanan terbanyak adalah ancaman partus prematurus. Penyakit neonatal terbanyak adalah caput succedaneum. AKI tahun 2014 adalah 298 kematian per 100.000 kelahiran hidup, tahun 2015 sampai bulan Juni terjadi peningkatan 387 kematian per 100.000 kelahiran hidup. AKB selama tahun 2014 adalah 371 kematian per 1.000 kelahiran hidup, tahun 2015 sampai bulan Juni terjadi peningkatan 453 kematian per 1.000 kelahiran hidup.Kata kunci: PONEK